Sexual Behaviors and PrEP Use Among Men Who Have Sex with Men: Systematic Literature Review - Sri Utami; Najmah Najmah; Rafiah Maharani Pulungan; Rini Mutahar; Rico Januar Sitorus (Health Information : Jurnal Penelitian, 2026)
Background: High-risk sexual behaviors among men who have sex with men (MSM) significantly contribute to the high incidence of HIV in Southeast Asia, while the utilization of Pre-Exposure Prophylaxis (PrEP) despite its proven effectiveness, remains suboptimal due to structural barriers and stigma. Objective: To analyze the relationship between sexual behavior and PrEP use among MSM in Southeast Asia. Methods: A Systematic Literature Review using PubMed and ScienceDirect for publications from 2015–2025. Of 308 identified articles, 10 met the inclusion criteria and were analyzed thematically. Results: High-risk sexual behaviors, including condomless anal intercourse and multiple sexual partnerships, were strongly associated with increased need for and interest in PrEP; however, PrEP uptake was limited by stigma, unsupportive regulations, and restricted access to sexual health services. Conclusion: High-risk sexual behavior is significantly associated with PrEP use. Suggestion: Expanding inclusive sexual health services, strengthening evidence-based education, and implementing supportive policies are essential to improve PrEP utilization and HIV prevention in the region.